The legal dimension in cold-war interactions : some notes from the field - Borisova, Tatʹi͡ana; Simons, William B. (Law in Eastern Europe ;, 2012)
This volume offers readers a stimulating perspective on both struggles and cooperation on the Cold-War's legal front and regard for its political context. It covers the era of Stalinism up to the post-Communist period of the 1990s and 2000s.